2017
DOI: 10.1108/f-10-2016-0094
|View full text |Cite
|
Sign up to set email alerts
|

Integrating contractor and property developer for product system innovations

Abstract: Purpose The aim of this paper is to explain why construction groups facing opportunities for product system innovations, such as green buildings, may choose to integrate construction and property development, taking on facilities management (FM) for a limited period. Design/methodology/approach Conceptual analysis based on prior literature and illustrated by a single case of integration. Findings For product system innovations, an in-house developer should be more able to reduce uncertainty than independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…Thus, managing in-house solves those problems that may arise when a service provider hired fails to perform and leads to better relationships with tenants because issues of FM get to the property owner directly via the in-house team. The results concerning innovation-related factors further support the findings of Holmén et al (2017) who examined why construction JFM 22,2 firms who are aspiring for product system innovations, such as green buildings and found that integrating in-house FM into their construction and property development business offers them more opportunities to be innovative.…”
Section: Drivers Of Facility Management Strategiessupporting
confidence: 76%
See 1 more Smart Citation
“…Thus, managing in-house solves those problems that may arise when a service provider hired fails to perform and leads to better relationships with tenants because issues of FM get to the property owner directly via the in-house team. The results concerning innovation-related factors further support the findings of Holmén et al (2017) who examined why construction JFM 22,2 firms who are aspiring for product system innovations, such as green buildings and found that integrating in-house FM into their construction and property development business offers them more opportunities to be innovative.…”
Section: Drivers Of Facility Management Strategiessupporting
confidence: 76%
“…According to Amos and Gadzekpo (2016) study on why most polytechnics in Ghana use in-house FM for most services, control over staff, processes and procedures was important and outsourcing offers less opportunity to achieve this because staff of outsourced service providers are often accountable to their employers. Another disadvantage associated with outsourcing is that it does not promote innovation within an organisation and can lead to technological redundancies because of overdependence on external service providers (Holmén et al , 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Amos and Gadzekpo (2016) study on why most technical universities in Ghana use in-house FM for most services, control over staff, processes and procedures was important and the in-house strategy offered a better opportunity to achieve this with flexibility than the outsourcing approach. Another advantage associated with the in-house FM approach is that it promotes innovation within the organisation and helps avoid technological redundancies that may arise when there is overdependence on external service providers (Tannor et al , 2022b; Holmén et al , 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The banks were particularly concerned about the security of their clients’ data when their ICT services were from third-party agents. In another study, Holmén et al (2017) were concerned that the use of agents for a long period of time makes the principal redundant, less innovative and over-dependent on the agents and any failure in the agent’s output could affect the overall output of the principal.…”
Section: Literature Reviewmentioning
confidence: 99%